Tanzimat Döneminde Kıbrıs Zaptiye Teşkilatı / Cyprus Zaptiyeh Establishment during the Tanzimat Era - Samani, Hasan; Onurkan Samani, Meltem (Journal of History Culture and Art Research, 2017)
Abstract During the Tanzimat (reform) period, which was a unique period in the history of Ottoman modernisation, many new institutions were established. The Tanzimat reforms also affected Cyprus, which had been an Ottoman island since 1571. One of the institutions was the Zaptiyeh (police) organization, formed to provide domestic security services.The Cyprus Zaptiyeh organization was established through various regulations implemented during the period between 1846-1871. At the beginning of process, the establishment of a Zaptiyeh squad was initiated. By 1870, a Zaptiyeh battalion composed of four squadrons, and attached to Cezâir-i Bahr-i Sefid (Mediterranean Islands) Province Regiment, was established in Cyprus. Throughout the Tanzimat period, the Cyprus Zaptiyeh organisation failed to meet the island’s domestic security services requirements. Therefore, the local authorities of Cyprus consistently sought to strenghten the organisation. In this context, the present study aims to investigate the process of the establishment of the Zaptiyeh organization based on the specific challenges in Cyprus. Öz Osmanlı yenileşme tarihinde özgün bir yere sahip Tanzimat döneminde kamu hizmetlerini yerine getirecek birçok yeni kurum oluşturulmuştur. 1571’den bu yana bir Osmanlı adası olan Kıbrıs’ta da Tanzimat’ın kurumsal yeniden yapılanmaya ilişkin yansımalarını görmek mümkündür. Bu dönemde yapılan düzenlemelerden bir tanesi de toplumun can ve mal güvenliğini sağlayacak modern bir iç güvenlik kurumu olarak Zaptiye Teşkilatı’nın kurulması olmuştur. Osmanlı geneliyle paralel olarak Kıbrıs’ta bir Zaptiye Teşkilatı’nın kuruluşu 1846-1871 arası dönemde yapılan çeşitli düzenlemelerle gerçekleşmiştir. Bu sürecin başında adada zaptiye birlikleri oluşturulmaya başlanmış, 1870 senesine gelindiğinde Kıbrıs’ta Cezâir-i Bahr-i Sefîd Vilayeti Zaptiye Alayı’na bağlı dört bölüklü bir Zaptiye Taburu teşkil edilmiştir. Tanzimat dönemi boyunca Kıbrıs’taki zaptiye birliği adanın iç güvenliğini sağlamada yetersiz kalmış, Kıbrıs’ın yerel idarecileri güçlendirilmesi için sürekli çaba sarf etmişlerdir. Bu bağlamda, mevcut çalışmada Kıbrıs’ta Zaptiye Teşkilatı’nın kurulması süreci, süreci olumsuz etkileyen çeşitli faktörlerle birlikte incelenmiştir.